Correlation between Her2/Neu and Histopatholoical Finding among Sudanese Female Breast Cancer Patients - Hamed, Riyadh; Abdelbadie, Ahmed; Osman, Ihsan; Eltayeb, El khazin; Omer, Husam Eldein (International Journal of Medical and Health Sciences Research, 2014)
Background: This study is one of very few studies which have investigated HER-2/neu expression and its correlation with histopathological finding. A total of 328 breast cancer tissue samples had been analyzed using immunohistochemical techniques. Objective: To compare the expression of tumor markers (HER-2/neu) with other prognostic parameters for mammary carcinomas. Results: Stage I- III B breast cancer HER-2/neu negative are (62%), whereas positive are (22%). Stage IV breast cancer HER-/neu negative are (4%), whereas positive are (3%). Recurrent breast cancer HER-2/neu negative are (3%) while positive are (5%).Stage I breast cancer HER-2/neu negative are (10%), whereas positive are (1%). Referring to stage II A, II B breast cancer HER-/neu negative are (59%), whereas positive are (16%). Stage III A, III B breast cancer HER-2/neu negative are (10%), while positive are (4%). HER-2/neu negative breast cancer Tumor size [le] 2 cm are (11%), while positive are (2%). HER-2/neu negative breast cancer Tumor size2-5 cm are (23%), whereas positive are (9%).HER-2/neu negative, Tumor size >5 cm are (26%), while positive are (29%). HER-2/neu negative breast cancer Nodal metastasis 0 are (5%), while positive are (2%). HER-2/neu negative Nodal metastasis1-9 are (16%), whereas positive are (19%). HER-2/neu negative breast cancer Nodal metastasis [ge] 10 are (28%), while positive are (30%). HER-2/neu negative histological subtype NIDC are (2%), whereas positive are (1%). HER-2/neu negative histological subtype IDC are (67%), while positive are (25%). HER-2/neu negative histological subtype ILC are (1%), whereas positive are (1%). Lastly, HER-2/neu negative with others histological subtype are (3%), whereas positive are (0%). HER-2/neu negative histological grade I are (6%), whereas positive are (2%). HER-2/neu negative histological grade II are (21%), while positive are (7%). Lastly, HER-2/neu negative histological grade II are (40%), whereas positive are (24%). HER-2/neu negative lympho-vascular invasion- are (71%), positive are (29%). HER-2/neu negative with lympho positive or vascular positive are (80%), While among positive are (16%). Conclusion: In this study population, the HER-2/neu expression its relation with histopathological finding determined.